Sosialisasi Tentang Investasi Untuk Warga Kembangan Utara Jakarta Barat - Swarmilah Hariani; Harnovinsah Harnovinsah; Venny Venny (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2019)
This community service activity is themed “Information about the Capital Market to North Kembangan residents in West Jakarta". The activity is carried out by providing an explanation of the meaning, role, and benefits of the Capital Market in the economy. The history, structure, and institutions related to the Capital Market were explained. The explanation also concerns the basic understanding of trading mechanisms in the Capital Market. The explanation was given by counseling followed by a discussion session, questions and answers from the participants. The results of this activity provide increased knowledge of citizens about the Capital Market, as measured by a questionnaire distributed before and after the activity that contains questions about the Capital Market. The results of the analysis of the questionnaire answers in the form of a comparison of the questionnaire showed a change in public knowledge about capital market investment. Keywords: capital market investment, financial literacy